Lobbying and the power of multinational firms - Andreas Polk; Armin Schmutzler; Adrian Müller (University of Zurich, Socioeconomic Institute, 2010)
Are national or multinational firms better lobbyists? This paper analyzes the extent of national environmental regulation when policy is determined in a lobbying game between a government and firm. We compare the resulting regulation levels for national and multinational firms. We identify three countervailing forces, the easier-to-shut-down effect, the easier-to-curb-exports effect and the multiple-plant effect. The interplay of these three forces determines whether national or multinational firms produce more, depending on such parameters as the potential environmental damages, transportation costs and the in uence of the firm. We also show that welfare levels are higher with multinational firms than with national firms when there is no lobbying, but that lobbying can reverse the welfare ordering.
Keywords: D72; F23; L51; 330; multinational enterprises; regulation; policy formation; lobbying; interest groups; foreign direct investment; Interessenpolitik; Multinationales Unternehmen; Interessenvertretung; Direktinvestition; Neue politische Ökonomie; Theorie